TRAFFIC FLOW ANALYSIS MKJI METHOD AT JALAN TRANS KM 33 KUALA KAPUAS CENTRAL - Lisa Hardika; Rosehan Anwar (Universitas Lambung Mangkurat, 2017)
Trans Kalimantan road is the liaison between the Province of central Kalimantan and South Kalimantan. Trans Kalimantan Road Km 33 is calculated by BM from Banjarmasin included in the Central Kalimantan region if by address, name is Jalan Trans Kalimantan km.10,5. Given the importance of the Trans Kalimantan Km.33 as land transport infrastructure, where the road was also no shops, markets, The Education Facility increased to make Volume Vehicle Specific hours and Settlement Region The fast growth, resulting in the emergence of movements - Traffic and Goods Movement. For that, need to do research the existing condition about: capacity, V/C ratio, Level of Service (ITP), is where the future costs road and in terms of how predictive condition going forward with Highway Capacity Manual Indonesia (MKJI), and other problems well as alternative problems that exist in the way it can be known. To review research methodology, conducted at sta.00 + 200-00 + 400 with primary and secondary data retrieval. The results obtained Existing Condition Namely on (DS) 0.45 ITP B, Prediction 5 Years 0.58 ITP C DS, DS 0,75 Predictions 10 Years ITP D. And handling the Best taxable income Next 10 Years is a ring road motorcycles with ITP B. Keywords: Capacity, Level of Service, Prediction, MKJI.